Genetic Causal Association Between 15 Micronutrients and 12 Obstetric-Related Diseases: A Mendelian Randomization Study - Lele Pan; Jing Zhang; Mingwei Chen; Li Yuan; Rong Chen; Lina Zhao (Biological Trace Element Research, 2024)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Predictive models of air temperatures inside a naturally ventilated vehicle transporting weaner pigs - Guoxing Chen; Guoqiang Zhang; Li Rong (Computers and Electronics in Agriculture, 2024)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Effect of long-term temperature-controlled rearing on growth traits and sexual maturity of common carp (Cyprinus carpio) - Yongming Li; Kuangxin Chen; Bin Gui; Cheng Yang; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Verifying the reliability of CFD domain decomposition technique on modelling the airflow field inside a naturally ventilated cattle barn - Guoxing Chen; Guoqiang Zhang; Li Rong (Biosystems Engineering, 2024)

Off-site production of plasma-activated water for efficient disinfection: The crucial role of high valence NOx and new chemical pathways - Zifeng Wang; Xiangyu Wang; Shenghang Xu; Renwu Zhou; Mingyan Zhang; Wanchun Li; Zizhu Zhang; Luge Wang; Jinkun Chen; Jishen Zhang; Li Guo; Dandan Pei; et al. (Water Research, 2024)

Progress in the application of Salmonella vaccines in poultry: A mini review - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2024)

Learning-guided cross-sampling for large-scale evolutionary multi-objective optimization - Haofan Wang; Li Chen; Xingxing Hao; Rong Qu; Wei Zhou; Dekui Wang; Wei Liu (Swarm and Evolutionary Computation, 2024)

Neutral purple soil acidification and mineralogical property changes due to long-term urea application in southwest China - Jun Xie; Dan Wang; Yuanxue Chen; Zhiqi Li; Wencai Dai; Rong Huang; Zifang Wang; Ming Gao (Soil and Tillage Research, 2024)

Contribution, absorption mode, and model prediction of atmospheric deposition to copper and lead accumulation in soybean - Min Li; Haotian Wang; Ziqi Chen; Hailong Liu; Huan Zhao; Xiuting Rong; Ruizhi Xia; Xiaozhi Wang; Jun Zhou (Science of The Total Environment, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Cadmium bioavailability in market nori and kelp: A comparison with rice and mechanisms underlying reduction in rice cadmium bioavailability with nori and kelp consumption - Xu Duan; Lei Zhou; Sheng-Zhi Chen; Xin-Ying Lin; Rong-Yue Xue; Xi-Mei Xue; Dongmei Zhou; Hong-Bo Li (Science of The Total Environment, 2024)

Cascading impacts of nitrogen deposition on soil microbiome and herbivore communities in desert steppes - Jingxi Liu; Mengmeng Zhu; Xiangfeng Shi; Cang Hui; Yurong Sun; Rong Zhang; Decai Jin; Zhihong Li; Honghao Chen; Zihua Zhao (Science of The Total Environment, 2024)

Invisible hazards: Exploring neonicotinoid contamination and its environmental risks in urban parks across China - Yongfeng Deng; Ruqin Shen; Xue Zhang; Yang Li; Xingguo Chen; Rong-Rong He; Hao Tian; Shuqin Tang; Xiang Luo; Jing Li; Wan-Yang Sun; Hongli Tan (Science of The Total Environment, 2024)

Effects of changing spatial scale on debris-flow hazard assessment: A case study in the Dadu River basin, China - Lili Zhang; Jianqiang Zhang; Zaiyang Ming; Haoyu Li; Rong Chen; Yang Jia (Science of The Total Environment, 2024)

Long-term cereal-legume intercropping accelerates soil organic carbon loss in subsoil of dryland - Wei Wang; Guang-Rong Chen; Meng-Ying Li; Yinglong Chen; Yang Wang; Hong-Yan Tao; Hui-Zhi Hou; Muhammad Maqsood Ur Rehman; Muhammad Ashraf; Yajie Song; Levis Kavagi; Bao-Zhong Wang; et al. (Resources, Conservation and Recycling, 2024)

Mechanism of β-MnO2 particle for the peroxymonosulfate activation under electric field: the promoting effect of carbamazepine on Mn(III) and reactive oxygen species production - Shaochun Yuan; Shuquan He; Qingyu Wu; Tuo Wang; Mengyu Li; Rong Liu; Yao Chen; Chuanliang Zhao; Fei Liu; Zhen Liu (Process Safety and Environmental Protection, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Soy protein isolate ameliorate gel properties by regulating the non-covalent interaction between epigallocatechin-3-gallate and myofibrillar protein - Ying Li; Yijun Zhang; Gongchen He; Ziyan Qiao; Rong Yang; Xi Zhou; Lin Chen; Xianchao Feng (Food Chemistry, 2024)

Quality improvement of threadfin bream (Nemipterus virgatus) surimi-gel using soy protein as a natural food additive - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Jing Yuan; Shinnosuke Maeda; Youjun Wang; Yan-Rong Jiang; Xiao-Mi Sun; Chao-Ping Chen; Yajun Wang; Tetsuhiko Okajima; Kiyoshi Osatomi (Food Chemistry, 2024)

MOF-derived S, N co-doped porous carbon matrix with single Fe atoms and CoSx nanoparticles dual-sites for enhanced oxygen reduction - Yu chen; Jian Rong; Jing Wu; Yuzhe Zhang; Huaisheng Ao; Xudong Zheng; Chao Jing; Ruilan Yang; Ziyao Zhou; Zhongyu Li (Chemical Engineering Journal, 2024)

Deciphering the role of biochar pseudocapacitance strengthening in promoting syntrophic methanogenesis: Microbial capacitance-tropism in propionate metabolism - Danyang Zhao; Lizi Ding; Xuemeng Wang; Qian Li; Feixiang Zan; Yu-You Li; Rong Chen (Chemical Engineering Journal, 2024)

Chemical constituents from noni (Morinda citrifolia L.) fruit juice and their chemotaxonomic significance - Yu-Qin Meng; Bin Zhang; Dong-Hui Zhang; Zhang-Xin Yu; Chun-Hua Long; Si-Rong Li; Xue-Na Zhang; Xiao-Bao Li; Guang-Ying Chen (Biochemical Systematics and Ecology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Single-cell transcriptome analysis of the mouse lungs during the injury and recovery periods after lipopolysaccharide administration - Hou-Ping Wang; Jian He; Jian-Rong He; Dan-Dan Li; He Huang; Bing Chen (Inflammation Research, 2024)

Amplification of warming-wetting in high mountains and associated mechanisms during the 21st century in Xinjiang, Central Asia - Rong Chen; Keqin Duan; Peihong Shi; Wei Shang; Junhua Yang; Jinping He; Yali Meng; Mingyu Dou; Liang Li (Climatic Change, 2024)

Unraveling fertilization effects on the dynamics of arbuscular mycorrhizal fungal community in the Qinghai-Tibet Alpine Meadow - Longfei Liu; Yi Ren; Shuo Sun; Chen Liu; Kairui Ding; Rong Li; Pengfei Zhang; Biao Shen; Mohammadhossein Ravanbakhsh; Wu Xiong; Qirong Shen (Soil Ecology Letters, 2024)

Nitrifying and denitrifying microbes exhibit distinct community structure and activity responses to different crop rotation systems in subtropical paddy soils - Huifang Xu; Ke Li; Rong Sheng; Hongling Qin; Yi Liu; Anlei Chen; Haijun Hou; Baoli Zhu; Wenxue Wei; Wenzhao Zhang (Applied Soil Ecology, 2024)

Preparation of amino-functionalized CoAl-LDH/palygorskite hierarchical composites for CO2 capture - Shixiang Zuo; Min Sun; Weifeng Gong; Tongtong Tang; Xuhua Ye; Wenjie Liu; Ngie Hing Wong; Rong Xu; Guihua Chen; Chao Yao; Haoguan Gui; Xiazhang Li (Applied Clay Science, 2024)

Active tectonic deformation and its seismic–geological significance of boundary faults of the Daxing Uplift and Langgu–Dachang Depression, Beijing Plain, China - Rong-Ying Zheng; Zhong-Yuan Yu; Bai-Xu Chen; Lu-Wei Li; Yi-Cheng Wang (Applied Geophysics, 2024)

Methylobacterium nigriterrae sp. nov., isolated from black soil - Le-Bin Chen; Yu-Ting OuYang; Lan Liu; Pin-Jiao Jin; Rong-Rong Huang; Wen-Yi Pan; Ying Wang; Jia-Ying Xing; Ting-Ting She; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Noradrenergic Projections from the Locus Coeruleus to the Medial Prefrontal Cortex Enhances Stress Coping Behavior in Mice Following Long-Term Intermittent Fasting - Zheng Zhao; Jun-Liang Chen; Han Zhan; Chang-Rong Fang; Li-Bo Hua; Hao-Yuan Deng; Zongqin Xiang; Ying Yang; Lang Huang; Yong U. Liu (NeuroMolecular Medicine, 2024)

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Experimental study on temperature difference between the interior and exterior of the vehicle transporting weaner pigs - Guoxing Chen; Cecilie Kobek-Kjeldager; Line D. Jensen; Jens K. Kristensen; Marianne Kaiser; Karen Thodberg; Guoqiang Zhang; Li Rong; Mette S. Herskin; Leslie Foldager (Biosystems Engineering, 2024)

Synergic treatment of domestic wastewater and food waste in an anaerobic membrane bioreactor demo plant: Process performance, energy consumption, and greenhouse gas emissions - Zhen Lei; Jiale Zheng; Jiale Liu; Qian Li; Jingjing Xue; Yuan Yang; Zhe Kong; Yu-You Li; Rong Chen (Water Research, 2024)

Unraveling phytoremediation mechanisms of the common reed (Phragmites australis) suspension cells towards ciprofloxacin: Xenobiotic transformation and metabolic reprogramming - Bin Wang; Hang Xu; Yu Liu; Kaiping Zhou; Xinyu Li; Deyang Kong; Jinmei Chen; Yujie He; Rong Ji (Water Research, 2024)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Improved global estimation of seasonal variations in C3 photosynthetic capacity based on eco-evolutionary optimality hypotheses and remote sensing - Yihong Liu; Jing M. Chen; Mingzhu Xu; Rong Wang; Weiliang Fan; Wenyu Li; Lucas Kammer; Colin Prentice; Trevor F. Keenan; Nicholas G. Smith (Remote Sensing of Environment, 2024)

Enhancing effect of conductive materials and rumen microorganisms on the anaerobic digestion performance of a real traditional Chinese medicine wastewater - Han Gao; Xiang-Lin Chang; Su Li; Rong Chen; Yu-You Li; Bao-Shan Xing (Journal of Water Process Engineering, 2024)

Accumulation and depuration of 4,5-dihydro-KmTx2 from Karlodinium veneficum in the bivalves, Mercenaria mercenaria and Sinonovacula constricta - Yanrong Li; Rong Chen; Zhujun Zhu; Tong Mu; Zhaoshou Ran; Jilin Xu; Chengxu Zhou; Xiaojun Yan (Harmful Algae, 2024)

Simple theranostics nanoagent for precision suppression of tumor growth and metastasis: A traditional fermented product having a novel functional breakthrough - Pengmin Liu; Rong Dai; Juan Li; Lin Chen; Qi Liu; Yuhang Wang; Shichao Meng; Binyue Zhang; Jinxuan Li; Weiwei Kang; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2024)

Experimental studies and pore-scale modeling of hydrate dissociation kinetics at different depressurization rates in a cubic hydrate simulator - Chang-Wen Xiao; Xiao-Sen Li; Hong-Feng Lu; Gang Li; Chen-Lu Xu; Rong-Rong Qi; Dong-Hui Xing; Xian Li; Yi-Fan Weng; Lu Yu (Chemical Engineering Journal, 2024)

Preparation of super toughened flame-retardant polylactic acid with an in situ hyperbranched structure by reactive blending with a phosphorus-containing copolyester and hexamethylene glycidyl cyclotriphosphazene - Guozhang Gu; Huaiyang Cai; Yutao Wang; Chen Tang; Guoxiang Zou; Jinchun Li; Rong Yang (Chemical Engineering Journal, 2024)

Green recycling of end-of-life photovoltaic modules via Deep-Eutectic solvents - Yuelong Yu; Shaoyuan Li; Jijun Lu; Fengshuo Xi; Xiuhua Chen; Dandan Wu; Wenhui Ma; Rong Deng (Chemical Engineering Journal, 2024)

Bioactives from biomass: Treasure for future potent antimicrobial applications - Weicheng Chen; Peng Zhang; Yucui Ding; Xiaobin Xie; Jianlong Fu; Rong Zhao; Yihan Xiao; Miodrag J. Lukic; Bin Li; Weishan Wang; Song Chen (Chemical Engineering Journal, 2024)

Ceftriaxone Removal with Sulfonic-phosphoric Acid Resin Based on Cation Adsorption Characteristic - Changlian Zheng; Min He; Bingqian Jia; Bin Chen; Rong Li (Water, Air, & Soil Pollution, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Biological exposure to microplastics and nanoplastics and plastic additives: impairment of glycolipid metabolism and adverse effects on metabolic diseases - Peng Chen Zheng; Rong Li; Keng Po Lai; Xiao Xi Zhang (Environmental Science and Pollution Research, 2024)

Early detection of fungal infection in citrus using biospeckle imaging - Si Yang; Chenxi Li; Xinyu Li; Jingying Jiang; Yansong Zhao; Xiaoli Wang; Wenliang Chen; Rong Liu; Kexin Xu (Computers and Electronics in Agriculture, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Isobavachin induces autophagy-mediated cytotoxicity in AML12 cells via AMPK and PI3K/Akt/mTOR pathways - Ning Xia; Qing-Hai Chen; Zhao-Jun Meng; Shu-Yue Ma; Jia-Li Huang; Rong Shen; Yu-Tong Dong; Hai-Wei Du; Kun Zhou (Toxicology in Vitro, 2024)

Organic fertilizer substitution benefits microbial richness and wheat yield under warming - Zheng-Rong Kan; Yinan Xu; Ahmad Latif Virk; Mengting Liu; Xinyu Pei; Yanling Li; Haishui Yang; Changqing Chen (Science of The Total Environment, 2024)

Ship autonomous collision avoidance decision from the perspective of navigation practice - Mengxia Li; Junmin Mou; Pengfei Chen; Hao Rong; Linying Chen; Xinya Zhao; Yong Wu (Ocean Engineering, 2024)

Interactions between fibroblasts and monocyte-derived cells in chronic lung injuries induced by real-ambient particulate matter exposure - Youjin Zeng; Rui Zhang; Yue Jiang; Daochuan Li; Liping Chen; Guanghui Dong; Rong Zhang; Yujie Niu; Wen Chen; Shen Chen (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Pollution area identification, receptor model-oriented sources and probabilistic health hazards to prioritize control measures for heavy metal management in soil - Ram Proshad; S.M. Asharaful Abedin Asha; Md Anwarul Abedin; Geng Chen; Ziyi Li; Shuangting Zhang; Rong Tan; Yineng Lu; Xifeng Zhang; Zhuanjun Zhao (Journal of Environmental Management, 2024)

Dicranopteris pedata improves soil quality by enhancing nutrient deposition, decreasing metal concentration, and boosting microbial diversity on abandoned rare earth elements mining sites - Xi-Wen Cui; Zhen-An Xu; Xian Chen; Zhi-Biao Chen; Jia-Bing Li; Rong-Rong Xie; Hong Zhang; Yong Zhang; Yong-He Han (Journal of Environmental Chemical Engineering, 2024)

Enhanced hydrate formation at the liquid CO2-brine interface with shear flow for solid CO2 sequestration - Ming-Long Wang; Yi-Fei Sun; Wei-Xin Pang; Qing-Ping Li; Ting Huang; Hong-Nan Chen; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Dan Rao; Bei Liu; Chang-Yu Sun; et al. (Gas Science and Engineering, 2024)

Gum arabic coating alleviates chilling injury of cold-stored peach by regulating reactive oxygen species, phenolic, and sugar metabolism - Zengyu Gan; Yupei Zhang; Ziteng Jin; Yongjie Wang; Jiali Li; Caining Yang; Qing Cao; Jinyin Chen; Zhenbang Rong; Xuming Lu; Suqin Guo (Food Chemistry, 2024)

Identification of peptides from Corneum Galli Gigeri Endothelium and inhibiting H2O2-induced gastric mucosa associated with the Rho signaling pathway - Rong xiang Guo; Huiying Zhang; Yao Chen; Pan Li; Bing Du (Food Bioscience, 2024)

N, S-carbon quantum dots as inhibitor in pickling process of heat exchangers for enhanced performance in multi-stage flash seawater desalination - Bochuan Tan; Yan Liu; Haiqin Ren; Zhili Gong; Xin Li; Wenpo Li; Lei Guo; Rong Chen; Juxiang Wei; Qingwei Dai; Abeer A. AlObaid (Desalination, 2024)

Enhanced solar-driven steam generation and water purification using 3D arch solar evaporators - Yong-Gang Wu; Chao-Hua Xue; Xiao-Jing Guo; Meng-Chen Huang; Hui-Di Wang; Chao-Qun Ma; Li Wan; Shi-Qiang Lv; Wen-Min Zhang; Rong-Rong Gao (Desalination, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Low oxygen adsorption energy barrier architectures to facilitate microenvironmental photocatalytic disinfection in Wei River - Lenan Yao; Yunyan Bai; Li Ding; Yayun Hu; Zuwang Zhang; Yajie Zhang; Rui Chen; Haijiao Xie; Jianlong Wang; Rong Wang (Chemical Engineering Journal, 2024)

Synergistic metabolism intervention and immune activation for antitumor therapy by biomineralized lactate oxidase - Yuxuan Ge; Zixin Wang; Yujia Lu; Fan Rong; Bin Hao; Zhao Li; Junsheng Chen; Yin Wang (Chemical Engineering Journal, 2024)

Quantifying the biodiversity and ecosystem service outcomes of karst ecological restoration: A meta-analysis of South China Karst - Yue Chen; Cai Cheng; Kangning Xiong; Li Rong; Shihao Zhang (CATENA, 2024)

Influenza A Virus PB1-F2 Induces Affective Disorder by Interfering Synaptic Plasticity in Hippocampal Dentate Gyrus - Saiying Wang; Haijun Zhang; Rui Liu; Peijun Han; Qi Yang; Caiyan Cheng; Yue Chen; Zheng Rong; Chang Su; Fei Li; Gaofei Wei; Minggao Zhao; et al. (Molecular Neurobiology, 2024)

Effects of Humic Acid-Copper Interactions on Growth, Nutrient Absorption, and Photosynthetic Performance of Citrus sinensis Seedlings in Sand Culture - Wei-Tao Huang; Qian Shen; Hui Yang; Xu-Feng Chen; Wei-Lin Huang; Han-Xue Wu; Ning-Wei Lai; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Journal of Plant Growth Regulation, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Investigating protistan predators and bacteria within soil microbiomes in agricultural ecosystems under organic and chemical fertilizer applications - Chen Liu; Zeyuan Zhou; Shuo Sun; Qi Zhang; Shiqi Sun; Xinnan Hang; Mohammadhossein Ravanbakhsh; Zhong Wei; Rong Li; Shimei Wang; Wu Xiong; George A. Kowalchuk; et al. (Biology and Fertility of Soils, 2024)
Organic farming can enhance biodiversity and soil health and is a sustainable alternative to conventional farming. Yet, soil protists especially protistan predators, have received inadequate attention, and their contributions to the sustainability of organic farming remained underexplored. In this study, we examined soil microbial communities from 379 samples, including both organic and chemically fertilized soils from China. Our findings revealed higher bacterial diversity and increases in plant-beneficial bacteria in organically farmed soils. Notably, organic farming systems facilitated dynamic predator-prey interactions, which may be disrupted by the application of chemical fertilizers. Additionally, organic farming enriched protistan predators, enhancing the relative abundance of functional PGPR, thus improving soil health. We further conducted a case study highlighting the critical role of organic matter in sustaining protistan predator populations and their interactions with bacteria. We propose the crucial contributions of organic inputs for supporting protistan predators and the interplay of predator-prey, ultimately enhancing soil functions and promoting agricultural sustainability.

Dual colorimetric platforms for direct detection of glyphosate based on Os-Rh nanozyme with peroxidase-like activity - Yingying Zhong; Junsong Yang; Wanying Wu; Haoyang Chen; Shuwei Li; Ziying Zhang; Shicheng Rong; Hongwu Wang (Analytica Chimica Acta, 2024)

Glutamine deprivation in glioblastoma stem cells triggers autophagic SIRT3 degradation to epigenetically restrict CD133 expression and stemness - Zhengcao Xing; Xianguo Jiang; Yalan Chen; Tiange Wang; Xiaohe Li; Xiangyun Wei; Qiuju Fan; Jie Yang; Hongmei Wu; Jinke Cheng; Rong Cai (Apoptosis, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Research progress on hepatotoxicity mechanism of polygonum multiflorum and its main components - Liping Gong; Xianhui Shen; Nana Huang; Kaiyi Wu; Rongrong Li; Ying Liu; Huijie Zhang; Siyi Chen; Rong Sun (Toxicon, 2024)

A pooled mycoviral resource in a strain of Rhizoctonia solani are regulators of fungal virulence - Ya Rong Wang; Jia En Su; Zhi Juan Yang; Jie Zhong; Xiao Gang Li; Yi Chen; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

Bamboo vinegar regulates the phytoremediation efficiency of Perilla frutescens (L.) Britt. by reducing membrane lipid damage and increasing cadmium retention - Zhenguo Li; Xingyu Hao; Tianlian He; Ying Chen; Mingwei Yang; Cheng Rong; Chengzhen Gu; Qingtie Xiao; Ruiyu Lin; Xinyu Zheng (Journal of Hazardous Materials, 2024)

p‑Phenylenediamine antioxidants in PM2.5: New markers for traffic in positive matrix factorization source apportionment - Nan Jiang; Xuexin Hao; Zichen Wang; Minzhen Li; Dong Zhang; Rong Cao; Ruiqin Zhang; Haijun Zhang; Jiping Chen; Ningbo Geng (Journal of Hazardous Materials, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Microplastics footprint in nature reserves-a case study on the microplastics in the guano from Yancheng Wetland Rare Birds National Nature Reserve, China - Huimin Jiang; Hai Cheng; Shiyue Wu; Hongshan Li; Hao Chen; Zhenghao Li; Xinyun Yao; Yanan Zhang; Yaqin Chen; Shuyi Chen; Shihao Chen; Liang Zheng; et al. (Environmental Research, 2024)

An investigation of a self-powered low-frequency nonlinear vibration isolation system - Ze-Qi Lu; Rong-Biao Hao; Dao Wu; Hu Ding; Li-Qun Chen (Engineering Structures, 2024)

Phthalocyanine J-aggregate nanoparticles with enormous-redshifted and intense absorption: Potential structure-J-aggregation relationships and application in tumor-associated macrophages-targeted phototheranostics - Fengxiang Tang; Haodong Yu; Yanzong Huang; Xue Zhao; Zixuan Chen; Honglin Ma; Bi-Yuan Zheng; Mei-Rong Ke; Yongfan Zhang; Xingshu Li; Juyoung Yoon; Jian-Dong Huang (Chemical Engineering Journal, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Superwetting MAX@SiO2 coatings with high photothermal conversion performances for efficient seawater desalination and anti-/de-icing - Helong Zhang; Chuxiong Qiu; Rong Zhang; Hao Zhang; Yunxia Chen; Tao Zeng; Fen Qiao; Lee Li; Ghafar Ali; Xiujian Zhao; Yi Xie (Chemical Engineering Journal, 2024)

Biokinetic and microbial insights into regulatory mechanisms of long-chain fatty acid degradation during food waste-lipid co-digestion within anaerobic membrane bioreactor - Yaqian Liu; Yu Xi; Qian Li; Mawuli Dzakpasu; Rong Chen; Yu-You Li (Bioresource Technology, 2024)

Nitrogen removal performance and mechanism in constructed wetlands under saline conditions: Role of Canna indica inoculated with Piriformospora indica - Naxin Cui; Min Cai; Xu Zhang; Rong Zeng; Li Zhou; Guifa Chen; Guoyan Zou (Bioresource Technology, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Development of a loading and diagnostic system to study laboratory earthquakes - Rong Chen; Ying Xu; Xuan Li; Wei Yao; Sheng Huang; Qi Zhao (Bulletin of Engineering Geology and the Environment, 2024)

Copper-ion-complexed palygorskite as a novel nanozyme with enhanced peroxidase-like activity for sensitive colorimetric sensing - Ping Chen; Hui Zhong; Xiao-rong Li; Tingting Zhang; Xiang Wang; Fang Hu; Yubo Yan; Jiaxing Xu; Meisheng Li (Applied Clay Science, 2024)

Application of luminescent Photobacterium Phosphoreum T3 for the detection of zearalenone and estimating the efficiency of their enzymatic degradation - Shu-Rong Chen; Li-Hong Chen; Li Pan; Bin Wang (Food Additives & Contaminants: Part A, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Temporal variations in dissolved organic matter properties in a eutrophic lake under water dilution and aquatic plant litter decomposition: A simulated microcosm study revealing the environmental and microbial driving factors - Rong Wu; Haoyu Wang; Wei Li; Xiaowan Chen; Qichao Zhou; Junjun Chang (Journal of Water Process Engineering, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Effects of polyphenols from walnut pellicle on the structure and allergenicity of walnut globulin - Jia-Hui Ma; Li-Qiu Ren; Tian-Xuan Tang; Yu-Yao Chen; Chen-Xi Zhang; Yu-Feng Ke; Yan Zhang; Mitchell N. Muskat; Xiang-Rong Cheng (Food Bioscience, 2024)

Suitable habitat evaluation and ecological security pattern optimization for the ecological restoration of Giant Panda habitat based on nonstationary factors and MCR model - Hui He; Xiangke Yu; Hui Yu; Zhigang Ma; Yong Luo; Tao Liu; Ziwei Rong; Jinhong Xu; Dianpeng Chen; Pengshang Li; Fuxin Yuan; Yongtao Zhao (Ecological Modelling, 2024)

Superior energy storage properties with prominent thermal stability in lead-free KNN-based ceramics through multi-component optimization strategy - Qifan Chen; Hao Chen; Dong Wang; Tingting Gao; Qinyu Li; Rong Lang; Zhi Tan; Jie Xing; Jianguo Zhu (Chemical Engineering Journal, 2024)

Regulatory mechanisms of biochar alleviating ammonia inhibition to methanogenesis during long-term operation of anaerobic membrane bioreactor treating swine wastewater - Bo Zhang; Gaojun Wang; Xiang Zhang; Peng Fu; Lu Chen; Yizhi Chen; Qian Li; Rong Chen (Chemical Engineering Journal, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Elevational distribution of forests and its spatiotemporal dynamics in subtropical China from 2000 to 2019 - Zhencan Zheng; Liuwen Zhuang; Guofang Miao; Han Liu; Zhiqiang Cheng; Wenyu Li; Rong Shang; Peng Gong; Jing Ming Chen (Science China Earth Sciences, 2024)

Identification of the Galactinol Synthase (GolS) Family in Medicago truncatula and Expression Analysis Under Abiotic Stress and Phytohormone Treatment - Hua Li; Ying Di Gao; Li Qing Kang; Hong Yang Yu; Li Ming Zeng; Yi Hua Wang; Rong Rong Chen; Jian Bo Song (Journal of Plant Growth Regulation, 2024)

Integrated Information for Pathogenicity and Treatment of Spiroplasma - Yixue You; Jianmin Xiao; Jiaxin Chen; Yuxin Li; Rong Li; Siyuan Zhang; Qichen Jiang; Peng Liu (Current Microbiology, 2024)

An origami microfluidic paper device based on core-shell Cu@Cu2S@N-doped carbon hollow nanocubes - Yuanyuan Li; Huinan Chen; Rong Huang; Dongmei Deng; Xiaoxia Yan; Liqiang Luo (Analytica Chimica Acta, 2024)

Deubiquitinating enzyme OTUD4 stabilizes RBM47 to induce ATF3 transcription: a novel mechanism underlying the restrained malignant properties of ccRCC cells - Ziyao Li; Ye Tian; Huafeng Zong; Xuelei Wang; Dongyang Li; Adili Keranmu; Shiyong Xin; Bowen Ye; Rong Bai; Weihua Chen; Guosheng Yang; Lin Ye; et al. (Apoptosis, 2024)

MicroRNA expression profile of chicken liver at different times after Histomonas meleagridis infection - Qiaoguang Chen; Yuming Zhang; Jie Rong; Chen Chen; Shuang Wang; Jiege Wang; Zaifan Li; Zhaofeng Hou; Dandan Liu; Jianping Tao; Jinjun Xu (Veterinary Parasitology, 2024)

Timing and Kinematics of late Cenozoic Strike-slip Faults in the Western Tibetan Plateau: New Constraints from Provenance Analysis and Detrital Thermochronology - Xiaochun Wei; Hanlin Chen; Rong Yang; Ping Wang; Shanying Li; Xuhua Shi; Jin Ge (Tectonophysics, 2024)

Toxic nonpreferred species accelerate the natural restoration of plant productivity and diversity in degraded grasslands - Xiaona Zheng; Chen Chen; Xin Dai; Le Lang; Xing Li; Jigui Chen; Rong Wang; Wenhui Cai; Ying Gao (Science of The Total Environment, 2024)

Biocontrol performance of a novel Bacillus velezensis L33a on tomato gray mold and its complete genome sequence analysis - Lixinyu Sun; Yu Chen; Shiyu Liu; Xiaogang Ou; Yangyang Wang; Zhengwu Zhao; Rong Tang; Yingzhe Yan; Xinyue Zeng; Shun Feng; Tao Zhang; Zhengguo Li; et al. (Postharvest Biology and Technology, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Electrocatalytic nitrate removal by non-precious three-dimensional Fe/Ni foam cathode: Experimental study and mechanism verification - Xiaodan Wang; Xi Ma; Yaoyao Wu; Chuanhao Li; Rong Chen (Journal of Water Process Engineering, 2024)

Divergent impacts of fertilization regimes on below-ground prokaryotic and eukaryotic communities in the Tibetan Plateau - Shuo Sun; Chen Liu; Yun Zhang; Yang Yue; Shiqi Sun; Yang Bai; Pengfei Zhang; Mohammadhossein Ravanbakhsh; Francisco Dini-Andreote; Rong Li; Zhenhua Zhang; Alexandre Jousset; et al. (Journal of Environmental Management, 2024)

Catalytic hydrotreatment of fast pyrolysis liquids from Pine wood using Ru-based catalysts supported on nitrogen-doped carbon materials - Yunhui Xia; Nan Xi; Xinyang Yu; Maohua Luo; Shi Chen; Qinglian Wang; Yixiong Lin; Rong Wang; Hao Li; Jun Yue; Chen Yang; Wang Yin; et al. (Fuel, 2024)

Fluoride exposure during puberty induces testicular impairment via ER stress-triggered apoptosis in mice - Rong Wang; Wenjing Gong; Yumeng Jiang; Qizi Yin; Ziyue Wang; Jie Wu; Mingming Zhang; Mengyuan Li; Yehao Liu; Juan Wang; Yuanhua Chen; Yanli Ji (Food and Chemical Toxicology, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

A deep learning network for improving predictions of maximum and minimum temperatures over complex terrain - Lin Xu; Li Zhou; He Chen; Rong-Hui Cai; Yue Zhou (Theoretical and Applied Climatology, 2024)

Strong ground motion characteristics of the 2022 MW 6.6 Luding earthquake and regional variability in ground motion among three earthquake areas in Sichuan, Southwest China - Bin Zhang; Xiaojun Li; Yanxiang Yu; Xiaojian Lu; Mianshui Rong; Su Chen; Zhao An; Zhenghui Xiong (Bulletin of Earthquake Engineering, 2024)

Multiple scenario land use simulation based on a coupled MOGA-PLUS model: a case of the Yellow River Basin - Guanghui Li; Yinghui Chang; Pengyan Zhang; Qianxu Wang; Zhuo Chen; Xinyue Zhang; Guangrui Xing; Rong Lu; Mengfan Li; Lei Gu (Environmental Science and Pollution Research, 2024)

NCOA4-mediated ferritinophagy participates in cadmium-triggered ferroptosis in spermatogonia - Didi Jia; Mingming Zhang; Mengyuan Li; Wenjing Gong; Wei Huang; Rong Wang; Yihang Chen; Qizi Yin; Jie Wu; Zhongxiu Jin; Juan Wang; Yehao Liu; et al. (Toxicology, 2024)

Long-term chemical and organic fertilization induces distinct variations of microbial associations but unanimous elevation of soil multifunctionality - Ke Li; Anlei Chen; Rong Sheng; Haijun Hou; Baoli Zhu; Wenxue Wei; Wenzhao Zhang (Science of The Total Environment, 2024)

Enhanced ammonia oxidation by a photoelectrocatalysis‑chlorine system: The role of ClO• and free chlorine - Xiaodan Wang; Xi Ma; Yaoyao Wu; Chuanhao Li; Rong Chen (Science of The Total Environment, 2024)

Capnesterones A and B, new steroids isolated from the soft coral Capnella imbricata - Ting-Yu Cheng; Chia-Jung Yang; Po-Jen Chen; Yu-Li Chen; Bo-Rong Peng; Te-An Kung; Zhi-Hong Wen; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

Removal of RNA viruses from swine wastewater using anaerobic membrane bioreactor: Performance and mechanisms - Yu Li; Baolei Wu; Xuanyu Zhai; Qian Li; Chenlong Fan; Yu-You Li; Daisuke Sano; Rong Chen (Journal of Hazardous Materials, 2024)

Biomineralization-inspired porous calcium carbonate microspheres as a controlled release system of herbicides/pesticides - Yaoxun Zeng; Xinyi Li; Fangzheng Chen; Huiling Ye; Keyi Rong; Zhili Ran; Binhong Liu; Zhenxing Pan; Xiuxian Xie; Junze Tang; Xujie Liu; Yan He (Journal of Environmental Chemical Engineering, 2024)

Effects of dietary supplementation with green lentil (Lens culinaris) hulls on NAFLD: Focus on intestinal and hepatic metabolism - Fanghua Guo; Dongying Chen; Rong Tsao; Fereidoon Shahidi; Hua Xiong; Hua Zhang; Li Jiang; Yong Sun (Food Bioscience, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Fibroblast-localized lncRNA CFIRL promotes cardiac fibrosis and dysfunction in dilated cardiomyopathy - Shuai Yuan; Xudong Zhang; Jiabing Zhan; Rong Xie; Jiahui Fan; Beibei Dai; Yanru Zhao; Zhongwei Yin; Qian Liu; Dao Wen Wang; Huaping Li; Chen Chen (Science China Life Sciences, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Draft Genome Sequence of Candida saopaulonensis from a Very Premature Infant with Sepsis - Ya-Ting Ning; Rong-Chen Dai; Zheng-Yu Luo; Meng Xiao; Yingchun Xu; Qun Yan; Li Zhang (Mycopathologia, 2024)
The rare fungus Candida saopaulonensis has never been reported to be associated with human infection. We report the draft genome sequence of the first clinical isolate of C. saopaulonensis, which was isolated from a very premature infant with sepsis. This is the first genome assembly reaching the near-complete chromosomal level with structural annotation for this species, opening up avenues for exploring evolutionary patterns and genetic mechanisms of pathogenesis.

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Dynamic causal modeling analysis reveals the modulation of motor cortex and integration in superior temporal gyrus during multisensory speech perception - Ting Zou; Liyuan Li; Xinju Huang; Chijun Deng; Xuyang Wang; Qing Gao; Huafu Chen; Rong Li (Cognitive Neurodynamics, 2024)
The processing of speech information from various sensory modalities is crucial for human communication. Both left posterior superior temporal gyrus (pSTG) and motor cortex importantly involve in the multisensory speech perception. However, the dynamic integration of primary sensory regions to pSTG and the motor cortex remain unclear. Here, we implemented a behavioral experiment of classical McGurk effect paradigm and acquired the task functional magnetic resonance imaging (fMRI) data during synchronized audiovisual syllabic perception from 63 normal adults. We conducted dynamic causal modeling (DCM) analysis to explore the cross-modal interactions among the left pSTG, left precentral gyrus (PrG), left middle superior temporal gyrus (mSTG), and left fusiform gyrus (FuG). Bayesian model selection favored a winning model that included modulations of connections to PrG (mSTG → PrG, FuG → PrG), from PrG (PrG → mSTG, PrG → FuG), and to pSTG (mSTG → pSTG, FuG → pSTG). Moreover, the coupling strength of the above connections correlated with behavioral McGurk susceptibility. In addition, significant differences were found in the coupling strength of these connections between strong and weak McGurk perceivers. Strong perceivers modulated less inhibitory visual influence, allowed less excitatory auditory information flowing into PrG, but integrated more audiovisual information in pSTG. Taken together, our findings show that the PrG and pSTG interact dynamically with primary cortices during audiovisual speech, and support the motor cortex plays a specifically functional role in modulating the gain and salience between auditory and visual modalities.

Efficient turn-on fluorescent probe cooperated by cascade response for disclosing the fluctuation of cysteine in cells - Li Meng; Zi Yi Xu; Jing Rong Chen; Hong Qun Luo; Nian Bing Li (Analytica Chimica Acta, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

CFD investigation on a novel pen partition-attached jet air supply for mitigating heat stress among lactating sows - Guoxing Chen; Guoqiang Zhang; Bjarne Bjerg; Poul Pedersen; Torben Jensen; Li Rong (Computers and Electronics in Agriculture, 2024)

Responses of phenology to preseason drought and soil temperature for different land cover types on the Mongolian Plateau - Bing Li; Rong Wang; Jing M. Chen (Science of The Total Environment, 2024)

Northward shift of Indian summer monsoon and intensifying winter westerlies cause stronger precipitation seasonality over Pamirs and its downstream basins in the 21st century - Jinping He; Keqin Duan; Shuangshuang Li; Wei Shang; Qiong Wang; Rong Chen; Yali Meng (Science of The Total Environment, 2024)

Synergistic effects of biochar addition and filtration mode optimization on mitigating membrane fouling in high-solid anaerobic membrane bioreactors - Chengfan Jiao; Hao Chen; Yaqian Liu; Hexiang Zhao; Qian Li; Gaojun Wang; Rong Chen; Yu-You Li (Science of The Total Environment, 2024)

Advances in understanding bioaerosol release characteristics and potential hazards during aerobic composting - Sai Yang; Yanan Yin; Wenrong Zhang; Haichao Li; Xiaochang Wang; Rong Chen (Science of The Total Environment, 2024)

Effects of typhoon events on coastal hydrology, nutrients, and algal bloom dynamics: Insights from continuous observation and machine learning in semi-enclosed Zhanjiang Bay, China - Peng Zhang; Huizi Long; Zhihao Li; Rong Chen; Demeng Peng; Jibiao Zhang (Science of The Total Environment, 2024)

Neural network establishes co-occurrence links between transformation products of the contaminant and the soil microbiome - Yuhui Xiang; Yansong Yu; Jiahui Wang; Weiwei Li; Yu Rong; Haibo Ling; Zhongbing Chen; Yiguang Qian; Xiaole Han; Jie Sun; Yuyi Yang; Liang Chen; et al. (Science of The Total Environment, 2024)

Massive early Middle Pleistocene cheetah from eastern Asia shed light onto the evolution of Acinonyx in Eurasia - Qigao Jiangzuo; Yaming Wang; Joan Madurell-Malapeira; Saverio Bartolini Lucenti; Shijie Li; Shiqi Wang; Zhaoyu Li; Rong Yang; Yi Jia; Lu Zhang; Shanqin Chen; Changzhu Jin; et al. (Quaternary Science Reviews, 2024)

The separate and synergistic role of biochar and electric field to facilitate mesophilic anaerobic digestion of food waste slurry - Gaojun Wang; Bo Zhang; Changxi Sun; Lu Chen; Kexin Wang; Qian Li; Rong Chen (Journal of Water Process Engineering, 2024)

Biodegradation of various grades of polyethylene microplastics by Tenebrio molitor and Tenebrio obscurus larvae: Effects on their physiology - Meng-Qi Ding; Jie Ding; Zhi-Rong Zhang; Mei-Xi Li; Chen-Hao Cui; Ji-Wei Pang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu; Shan-Shan Yang (Journal of Environmental Management, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

Modifying duck myofibrillar proteins using sodium bicarbonate under cold plasma treatment: Impact on the conformation, emulsification, and rheological properties - Shengqi Jiang; Chunjie Yang; Rong Bai; Ziwei Li; Linlu Zhang; Ya Chen; Xiang Ye; Siying Wang; Hao Jiang; Wu Ding (Food Hydrocolloids, 2024)

An injectable antibacterial hydrogel with bacterial-targeting properties for subcutaneous suppuration treatment - Yongchang Tian; Rong Zhang; Jiaming Cui; Yaowei Zhu; Minghui Sun; Ian W. Hamley; Chunsheng Xiao; Li Chen (Chemical Engineering Journal, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Contact-electro-catalysis for degradation of trace antibiotics in wastewater - Da-Qi Cao; Rong-Kun Fang; Yi-Xuan Song; Ming-Guo Ma; Haiyan Li; Xiao-Di Hao; Rongling Wu; Xiangyu Chen (Chemical Engineering Journal, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Enhancing biohydrogen production from xylose through natural FeS2 ore: Mechanistic insights - Yun Xu; Miao-yu Deng; Si-jia Li; Yi-cheng Yuan; Hao-yu Sun; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2024)

Ceria nanoparticles: biomedical applications and toxicity - Xiaoxuan Fu; Peng Li; Xi Chen; Yuanyuan Ma; Rong Wang; Wenxuan Ji; Jiakuo Gu; Bowen Sheng; Yizhou Wang; Zhuhong Zhang (Journal of Zhejiang University-SCIENCE B, 2024)

The phylogenetic analysis of two invasive Trapa species in the United States revealed by chloroplast genomes and morphological traits - Xiang-Rong Fan; Nancy Rybicki; Lynde L. Dodd; Jie Min; Wei Li; Xiu-Ling Li; Godfrey Kinyori Wagutu; Yuan-Yuan Chen (Biological Invasions, 2024)

LSTM-based deformation forecasting for additional stress estimation of existing tunnel structure induced by adjacent shield tunneling - Xiao-Wei Ye; Si-Yuan Ma; Zhi-Xiong Liu; Yan-Bo Chen; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2024)

A specific module of ESCRT regulates STING activity termination by controlling STING degradation - Yuan Zhao; Chenxuan Zhou; Wenmin Tian; Yang Chen; Chongchong Zhao; Yan Li; Shixuan Wang; Yueguang Rong (Science Bulletin, 2024)

Geochemistry and P-T-t evolution of Paleoproterozoic metapelites of the Zhengjiapo BIF-type iron mine, Jiaobei terrane, North China Craton - Yan-Rong Chen; Xu-Ping Li; Zeng-Sheng Li; Da-Peng Li; Fan-Mei Kong; Hans-Peter Schertl; Yan-Jing Chen (Precambrian Research, 2024)

ALKBH5 SUMOylation-mediated FBXW7 m6A modification regulates alveolar cells senescence during 1-nitropyrene-induced pulmonary fibrosis - Se-Ruo Li; Ning-Ning Kang; Rong-Rong Wang; Meng-Die Li; Li-Hong Chen; Peng Zhou; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Boron-mediated amelioration of copper toxicity in Citrus sinensis seedlings involved reduced concentrations of copper in leaves and roots and their cell walls rather than increased copper fractions in their cell walls - Huan-Huan Chen; Zhi-Chao Zheng; Dan Hua; Xu-Feng Chen; Zeng-Rong Huang; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2024)

An integrated calibration strategy for the development and validation of an LC-MS/MS method for accurate quantification of egg allergens (Gal d 1–6) in foods - Shupeng Yang; Jingjing Chen; Mohamed F. Abdallah; Haopeng Lin; Peijie Yang; Jianxun Li; Rong Zhang; Qianqian Li; Peng Lu; Shuyan Liu; Yi Li (Food Chemistry, 2024)

Synchronous fluorescence spectra-based machine learning algorithm with quick and easy accessibility for simultaneous quantification of polycyclic aromatic hydrocarbons in edible oils - Jia-Wen Wei; Jia-Rong He; Shi-Yi Chen; Yi-Han Guo; Xuan-Zhu Huo; Nuan Zheng; Shuo-Hui Cao; Yao-Qun Li (Food Control, 2024)

Biochar-mediated synergistic promotion of DIET and IHT: Kinetic and thermodynamic insights into propionate two-step syntrophic methanogenesis - Danyang Zhao; Peiyun Zhang; Yaqian Liu; Qian Li; Gaojun Wang; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2024)

A robust Zr(IV)-based metal-organic framework featuring high-density free carboxylic groups for efficient uranium recovery - Bin Wang; Chunyu Bao; Jiahui Xu; Yunnan Tao; Long Chen; Duo Zhang; Kui Tan; Shuao Wang; Jian-Rong Li; Shengqian Ma (Chemical Engineering Journal, 2024)

In-situ GSH-responsive gas nanogenerator for active NIR-II FL/PA imaging and synergistic restoration the macrophage niche in rheumatoid arthritis - Xiaochun Zheng; Weiwei Kang; Yarong Jin; Xin Zhang; Wenxuan Wang; Dongsheng Li; Shutong Wu; Lin Chen; Shichao Meng; Rong Dai; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2024)

Fine mapping and candidate gene analysis of qSRC3 controlling the silk color in maize (Zea mays L.) - Xueying Wang; Yang Zhou; Chong You; Jinchang Yang; Zhengjie Chen; Dengguo Tang; Jixing Ni; Peng Li; Le Wang; Kaili Zhu; Wujiao Deng; Haimei Wu; et al. (Theoretical and Applied Genetics, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Effective recovery of the nitritation process through hydrogen peroxide - Cuilan Deng; Zhenguo Chen; Yonggan Li; Haochuan Chen; Yongxing Chen; Songwei Zhou; Rong Niu; Yuemin Tan (Environmental Science and Pollution Research, 2024)

Copper-doped Lanthanide Coordination Polymers as Luminescent Nanoenzyme for Ratiometric Sensing of H2O2 and Glutathione - Xinru Wu; Chen Ruan; Xinyue Zhu; Lina Zou; Rong Wang; Gaiping Li (Journal of Fluorescence, 2024)

Conductive nanofiltration membranes via in situ PEDOT-polymerization for electro-assisted membrane fouling mitigation - Tian-Zhi Jia; Ru Feng; Chun Cui; Qian Chen; Levente Cseri; Rong-Fei Zhou; Gyorgy Szekely; Xue-Li Cao; Shi-Peng Sun (Water Research, 2024)

Phytoremediation and environmental effects of three Amaranthaceae plants in contaminated soil under intercropping systems - Rong Huang; Chen Xing; Yuanru Yang; Wang Yu; Liangbin Zeng; Yanqiong Li; Zhijian Tan; Zhian Li (Science of The Total Environment, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Reservoir characteristics and controlling factors of the middle–high maturity multiple lithofacies reservoirs of the Lianggaoshan Formation shale strata in the northeastern Sichuan basin, China - Xin Wang; Min Wang; Chen Zhao; Xinyi Yang; Yidong Jia; Rong Wu; Tianyi Li; Xinbin Zhao; Yulong Tang (Marine and Petroleum Geology, 2024)

Geomorphic expression of transverse drainages across the Tugerming anticline, southern Tian Shan: Implications for the river-fold interaction in the foreland - Feng Li; Xuhua Shi; Julien Charreau; Xiaogan Cheng; Rong Yang; Hanlin Chen; Jin Ge; Jinghan Wang (Journal of Structural Geology, 2024)

Enhanced detection of acrylamide using a versatile solid-state upconversion sensor through spectral and visual analysis - Yawen Rong; Md Mehedi Hassan; Jizhong Wu; Shuo Chen; Wancheng Yang; Yunhao Li; Jiaji Zhu; Jun Huang; Quansheng Chen (Journal of Hazardous Materials, 2024)

Intraparticle sorption and desorption of antibiotics - Cheng Zhang; Rong Li; Dongfang Ke; Hongri Suo; Shuai Wang; Enze Ma; Yulong Chen; Chongxuan Liu (Journal of Hazardous Materials, 2024)

High-throughput analytical methodology of monoalkyl phthalate esters and the composite risk assessment with their parent phthalate esters in aquatic organisms and seawater - Qiang-Qiang Shi; Feng Xu; Tao Shen; Rong-Rong Zhang; Hua Liu; Ming-Ze Chen; Ai-Li Sun; Ze-Ming Zhang; Xi-Zhi Shi (Journal of Hazardous Materials, 2024)

Biochar improves the humification process during pig manure composting: Insights into roles of the bacterial community and metabolic functions - Yanan Yin; Xiaohui Tao; Yifei Du; Mengtong Li; Sai Yang; Wenrong Zhang; Chao Yang; Haichao Li; Xiaochang Wang; Rong Chen (Journal of Environmental Management, 2024)

Rapid colorimetric and fluorescence identification of Pinelliae Rhizoma and adulterate Rhizoma Typhonii Flagelliformis using direct-LAMP assay - Huilin Li; Jiaqi Cui; Hongling Chen; Hongying Li; Yuchen Xie; Wenjun Song; Rong Chen (Food Chemistry, 2024)

The optimal ammonium-nitrate ratio for various crops : A Meta-analysis - Jiatao Chen; Jinghua Li; Weifang Li; Peng Li; Rong Zhu; Yuxiu Zhong; Weifeng Zhang; Tingyu Li (Field Crops Research, 2024)

Re-evaluating the impact of feeding shock on anaerobic co-digestion of food waste and waste activated sludge: Trade-off between efficiency and stability - Yaqian Liu; Qian Li; Mawuli Dzakpasu; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2024)

Stereoisomerically enhanced polynorbornene-imide dielectric energy storage performance - Hongmei Qin; Man Liu; Shiyu Qin; Shixian Zhang; Xingnan Zhou; Chenjian Li; Yuhao Wei; Dan Chen; Rong Fan; Shan Wang; Quanling Yang; Chuanxi Xiong; et al. (Chemical Engineering Journal, 2024)

Damming-associated landscape change benefits a wind-dispersed pioneer plant species - Hang Ji; Yong-Rong He; Hong-Yue Li; Ling Lu; Jia-Hui Li; Jie Zou; Rong Wang; Jun-Yin Deng; Xiao-Yong Chen (New Forests, 2024)

MiR-26b-3p Promotes Intestinal Motility Disorder by Targeting FZD10 to Inhibit GSK3β/β-Catenin Signaling and Induce Enteric Glial Cell Apoptosis - Yu Zhan; Yong Wen; Fan Zheng; Li-juan Du; Tai-yu Chen; Xu-long Shen; Rong Wu; Xue-gui Tang (Molecular Neurobiology, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Epidural administration of large dose of opioid μ receptor agonist may impair cardiac functions and myocardial viability via desensitizing transient receptor potential vanilloid 1 - Xiang Ma; Zheng Guo; Mu-Rong Li; Lu Chen; Xing Zhao; Tian-Qi Wang; Tao Sun (Toxicology and Applied Pharmacology, 2024)

Chronic Pb exposure impairs learning and memory abilities by inhibiting excitatory projection neuro-circuit of the hippocampus in mice - Rong-Xin Zou; Xiaozhen Gu; Chenqing Huang; Hui-Li Wang; Xiang-tao Chen (Toxicology, 2024)

Effects of combined exposure to polystyrene microplastics and 17α-Methyltestosterone on the reproductive system of zebrafish - Weiya Rong; Yue Chen; Zijun Xiong; Haiyan Zhao; Tongyao Li; Qing Liu; Jing Song; Xianzong Wang; Yu Liu; Shaozhen Liu (Theriogenology, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Comparative study on anthropogenic impacts on soil PAHs: Accumulation and source apportionment in tourist and industrial cities in Hebei Province, China - Tian Xie; Meie Wang; Rong Jiang; Lei Li; Xinyue Chen; Suriyanarayanan Sarvajayakesavalu; Weiping Chen (Science of The Total Environment, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Emerging technology effects on combined agricultural and eco-vermicompost - Syed Turab Raza; Adugna Feyissa; Rong Li; Eldon R. Rene; Zulfiqar Ali; Hassan Iqbal; Zulfiqar Ali Sahito; Zhe Chen (Journal of Environmental Management, 2024)

Comparing the mechanisms of syntrophic volatile fatty acids oxidation and methanogenesis recovery from ammonia stress in regular and biochar-assisted anaerobic digestion: Different roads lead to the same goal - Gaojun Wang; Peng Fu; Yan Su; Bo Zhang; Mengyuan Zhang; Qian Li; Jianfeng Zhang; Yu-You Li; Rong Chen (Journal of Environmental Management, 2024)

Calcium ions induced ι-carrageenan-based gel-coating deposited on zein nanoparticles for encapsulating the curcumin - Qingyuan Ge; Shuang Rong; Chenxi Yin; David Julian McClements; Qi Fu; Qi Li; Yahong Han; Fuguo Liu; Suqing Wang; Shuai Chen (Food Chemistry, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Double crosslinked networks waterborne polyurethane with self-healing, recyclable and antibacterial functions based on dynamic bonds and used for temperature/light sensor - Wenhua Zeng; Yong Jin; Rong Zhou; Yupeng Li; Haonan Chen (Chemical Engineering Journal, 2024)

Negative thermopower anisotropic ionic thermoelectric hydrogels based on synergistic coordination and hydration for low-grade heat harvesting - Luzheng Chen; Xuhui Rong; Zhuqing Liu; Qijun Ding; Xia Li; Yifei Jiang; Wenjia Han; Jiang Lou (Chemical Engineering Journal, 2024)

Biochar’s role to achieve multi-pathway nitrogen removal in anammox systems: Insights from electron donation and selective microbial enrichment - Jingwei Fu; Qian Li; Mawuli Dzakpasu; Yifei He; Pengyu Zhou; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2024)

Preparation of potential organic fertilizer rich in γ-polyglutamic acid via microbial fermentation using brewer's spent grain as basic substrate - Fengqing Wang; Yanmei Chen; Jia Zheng; Can Yang; Li Li; Rong Li; Meilin Shi; Zhongxuan Li (Bioresource Technology, 2024)

Relationships between different types of biochar and N2O emissions during composting based on roles of nosZ-carrying denitrifying bacterial communities enriched on compost and biochar particles - Yanan Yin; Mengjin Gu; Wenrong Zhang; Chao Yang; Haichao Li; Xiaochang Wang; Rong Chen (Bioresource Technology, 2024)

Multi-scale feature learning via residual dynamic graph convolutional network for hyperspectral image classification - Rong Chen; Gemine Vivone; Guanghui Li; Chenglong Dai; Jocelyn Chanussot (International Journal of Remote Sensing, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Sex-dependent effects of rice cadmium exposure on body weight, gut microflora, and kidney metabolomics based on a mouse model - Jin-Lei Yang; Shan Chen; Jin-Feng Xi; Xin-Ying Lin; Rong-Yue Xue; Lena Q. Ma; Dongmei Zhou; Hong-Bo Li (Science of The Total Environment, 2024)

Enhancing the removal of chlorinated hydrocarbons from groundwater using a new BL5 microorganism with functional CS@ZVI materials - Zhiguo Chen; Wenqing Cao; Yan Li; Jingpeng Song; Yiyun Liu; Juncheng Liu; Rong Zhang; Rongxin Su; He Bai (Journal of Water Process Engineering, 2024)

Exploring carbon content variation in microplastics sequestrated from seawater to sediment in the Haima cold seep area - Xiao-Nan Wu; Jing-Chun Feng; Xiao Chen; Can-Rong Li; Si Zhang (Journal of Hazardous Materials, 2024)

A novel approach for evaluating the transport capacity of sandstone carriers and determining effective hydrocarbon migration channels: Application to the Pinghu Slope Belt of the Xihu Depression, East China Sea Basin - Fuwei Wang; Dongxia Chen; Meijun Li; Zhangxin Chen; Qiaochu Wang; Khawaja Hasnain Iltaf; Sha Li; Wenzhi Lei; Mengya Jiang; Yuqi Wang; Lanxi Rong (Journal of Asian Earth Sciences, 2024)

Visualized test of environmental water pollution and meat freshness: Design of Au NCs-CDs-test paper/PVA film for ratiometric fluorescent sensing of sulfide - Yi Huang; Shiming Chen; Wei Huang; Xiaoting Zhuang; Jiahao Zeng; Mingcong Rong; Li Niu (Food Chemistry, 2024)

Preparation of size-tunable Fe3O4 magnetic nanoporous carbon composites by MOF pyrolysis regulation for magnetic resonance sensing of aflatoxin B1 with excellent anti-matrix effect - Zhou Xu; Yanqiu Chen; Rong Wang; Maolong Chen; Jian Zhang; Yunhui Cheng; Bangben Yao; Li Yao; Jianguo Xu; Wei Chen (Food Chemistry, 2024)

Insights into current bio-processes and future perspectives of carbon-neutral treatment of industrial organic wastewater: A critical review - Xinzheng Zhang; Yuqin Fan; Tianwei Hao; Rong Chen; Tao Zhang; Yong Hu; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Environmental Research, 2024)

Exposure levels and determinants of placental polybrominated diphenyl ethers in Chinese pregnant women - Yijun Liu; Yan Xie; Yingkuan Tian; Juan Liao; Derong Fang; Linglu Wang; Rong Zeng; Shimin Xiong; Xingyan Liu; Qing Chen; Ya Zhang; Hongyu Yuan; et al. (Environmental Research, 2024)

Mechanistic insights into synergistic facilitation of copper/zinc ions and dewatered swine manure-derived biochar on anaerobic digestion of swine wastewater - Gaojun Wang; Changxi Sun; Peng Fu; Bo Zhang; Jinglin Zhu; Qian Li; Jianfeng Zhang; Rong Chen (Environmental Research, 2024)

Multiscale computational fluid dynamics modelling of spatial ALD on porous li-ion battery electrodes - Zoushuang Li; Yuanxiao Chen; Yufeng Nie; Fan Yang; Xiao Liu; Yuan Gao; Bin Shan; Rong Chen (Chemical Engineering Journal, 2024)

Nrf2 suppresses erastin-induced ferroptosis through activating system Xc(-) in ovarian cancer - Yongkang Li; Rong Yin; Miao Liang; Cheng Chen (Molecular & Cellular Toxicology, 2024)

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)